Follow-up practices for high-grade extremity Osteosarcoma. Issue 1 (December 2016) - Rothermundt, Christian; Seddon, Beatrice; Dileo, Palma; Strauss, Sandra; Coleman, Joanne; Briggs, Timothy; Haile, Sarah; Whelan, Jeremy
Abstract Background The optimal conduct of follow-up (FU) of patients with osteosarcoma is uncertain. In the absence of any formal validation of optimal timing and method of surveillance, guidance is provided by oncology societies' recommendations. FU is designed to detect either local recurrence or metastatic disease at a time when early treatment is still possible and might be effective. Methods We performed a retrospective analysis of 101 patients with high-grade extremity osteosarcoma in a single centre. Chest x-ray (CXR) was used as routine surveillance method; however patients with initial lung metastases or previous suspicious findings had computed tomography (CT) scans. Results With a median FU time of 30.7 months 34 patients relapsed. Relapse–free survival after 5 years was 61 % (CI 52 %; 73 %), late relapses occurred in only two patients between 2 and 5 years of FU. Twenty-five of the 34 relapses were detected at routine FU appointments. All 8 local recurrences were noted clinically. Twenty-two patients had metastases confined to the lungs, either detected on CXR or CT. Thirty-two percent of patients with lung metastases only were salvaged successfully. Conclusions Routine FU in high-grade osteosarcoma results in clinical detection of local relapse, and detection of lung metastases by CXR at a time when metastatectomy is possible. The optimal time interval for FU appointments is not known, however we recommend more frequent surveillance visits during the two years after treatment. We hypothesize that routine CT scans are not required and propose CXR for detection of lung metastases.